Endoscopic resection for verrucous venous malformation and capillary arteriovenous malformation: a deep approach to superficial lesions - Guo, Zhengtuan; Xie, Chong; Lin, Weilong; Wang, Peihua; Yang, Weijia; Wang, Huaijie (Frontiers in Surgery, 2025)
BackgroundOpen surgery is the treatment of choice for verrucous venous malformation (VVM) and capillary arteriovenous malformation (CAVM) with overgrowth. The study aimed to report an innovative endoscopic resection technique for subcutaneous vascular malformations with superficial lesions at our center.MethodsWe retrospectively reviewed the medical records of patients who underwent endoscopic resection for VVM or CAVM between September 2019 and July 2024.ResultsThe current cohort includes 14 female and 4 male patients, with ages ranging from 1 year to 8 years. Diagnoses included classic VVM (n = 10), VVM—subcutaneous variant (n = 4), and CAVM (n = 4). Endoscopic surgery uses two or more small ports in a gas-inflated manner. Surgery included radical resection, partial resection of the subcutaneous mass, and debulking of adipose overgrowth. Technical success was achieved in all patients. Local skin necrosis (area <1 cm2) occurred in two patients. No recurrence was observed during follow-up.ConclusionEndoscopic resection is a minimally invasive, feasible, and safe technique for VVMs in selected CAVM. Better cosmetic results can be expected in patients with superficial lesions using this endoscopic surgical technique.